2020
DOI: 10.7546/nntdm.2020.26.4.136-153
|View full text |Cite
|
Sign up to set email alerts
|

Properties of hyperbolic generalized Pell numbers

Abstract: In this paper, we introduce the generalized hyperbolic Pell numbers over the bidimensional Clifford algebra of hyperbolic numbers. As special cases, we deal with hyperbolic Pell and hyperbolic Pell–Lucas numbers. We present Binet’s formulas, generating functions and the summation formulas for these numbers. Moreover, we give Catalan’s, Cassini’s, d’Ocagne’s, Gelin–Cesàro’s, Melham’s identities and present matrices related to these sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…They also gave some important features of these newly defined numbers. Soykan and Göcen (Soykan and Göcen, 2020) introduced the generalized hyperbolic Pell numbers over the bidimensional Clifford algebra of hyperbolic numbers. Azak and Güngör (Azak and Güngör, 2017) defined the dual complex Fibonacci and Lucas numbers and gave the wellknown properties for these numbers.…”
Section: Introductionmentioning
confidence: 99%
“…They also gave some important features of these newly defined numbers. Soykan and Göcen (Soykan and Göcen, 2020) introduced the generalized hyperbolic Pell numbers over the bidimensional Clifford algebra of hyperbolic numbers. Azak and Güngör (Azak and Güngör, 2017) defined the dual complex Fibonacci and Lucas numbers and gave the wellknown properties for these numbers.…”
Section: Introductionmentioning
confidence: 99%
“…The literature contains many articles that related to the special number sequences such as Fibonacci, Lucas, Pell ( [2,3,6,8,14,15,17,18]). One of these articles goes through to the bi-periodic Fibonacci (or, equivalently, generalized Fibonacci) and the bi-periodic Lucas (or, equivalently, generalized Lucas).…”
Section: Introductionmentioning
confidence: 99%
“…Pell sequence has been studied by many authors and more detail can be found in the extensive literature dedicated to these sequences, see for example, [22], [23], [24], [25], [26], [27], [28], [29]. For higher order Pell sequences, see [30], [31], [32], [33], [34], [35].…”
Section: Introductionmentioning
confidence: 99%